Measures of differentiation and integration: One step closer to consciousness. (23rd March 2022) - Massimini, Marcello; Sarasso, Simone; Casarotto, Silvia; Rosanova, Mario
Abstract: Interpreting empirical measures of integration and differentiation as indices of cortical performance and memory consolidation during wakefulness rather than consciousness per se is inconsistent with the literature. Recent studies show that these theory-inspired measures can dissociate from such processes and reliably index the brain's capacity for experience. We consider this as a positive trend in consciousness research.